2002
DOI: 10.1002/rcm.761
|View full text |Cite
|
Sign up to set email alerts
|

Identification of compound classes in soil and peat fulvic acids as observed by electrospray ionization tandem mass spectrometry

Abstract: Soil and peat fulvic acids obtained from the International Humic Substances Society were fractionated by their solubility in methanol and analyzed by electrospray ionization tandem mass spectrometry. Precursor and product ion experiments produced mass spectra that indicated the presence of benzene, phenol, dihydroxy benzene, furan and thiophene carboxylic acids. Standards were used to substantiate the fragmentation patterns observed in the product ion spectra of the fulvic acid samples. This study makes signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…HS can be now represented as aggregates of aromatic molecules (mostly phenolic) carrying a large number of carboxylic functions (14)(15)(16). The cohesion of these aggregates is through more or less weak bonding including van der Walls interactions or hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…HS can be now represented as aggregates of aromatic molecules (mostly phenolic) carrying a large number of carboxylic functions (14)(15)(16). The cohesion of these aggregates is through more or less weak bonding including van der Walls interactions or hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…50% of the available Th(IV) ion concentration has been sorbed onto the cross-linked sample indicates that the remaining Th(IV) ion concentration exists as free ions in solution, suggesting that the increase in sorption of Th(IV) ions onto the original montmorillonite over the pH range 2-4 cannot be attributed to surface precipitation. Murphy et al (1999) investigated the sorption of Th(IV) ions onto hematite and found that sorption increased from ca. 0% to 100% over the pH range 1-4.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Since fulvic acids are polyelectrolitic compounds with carboxylic and phenol hydroxilic functional groups (McIntyre et al, 2002), they can influence the transport of inorganic and organic pollutants in water and soil (Hayes and Clapp, 2001;Kaschl et al, 2002). Especially due to its solubility, fulvic acid can infiltrate into seepage water.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new techniques, like solid-state C-13 NMR and pyrolysis gas chromatography with mass spectrometric detection (Schnitzer, 2001;Joly et al, 2000) or pyrolysis field ionization mass spectrometry (Schnitzer, 2001), electrospray tandem ionization mass spectrometry (Kujawinski et al, 2002;Leenheer et al, 2001;McIntyre et al, 2002) have permitted the structural and molecular elucidation of different humic substances, including also those of fulvic acid. Some of these techniques not only give the possibility of analyses of isolated fractions of humic substances, but even in situ analysis of the soils of their provenance (Schnitzer, 2001).…”
Section: Introductionmentioning
confidence: 99%